Pengaruh Pemanfaatan Sistem Informasi Akuntansi Keuangan Daerah dan Sistem Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah di Desa Se-Kecamatan Tambak Gresik Jawa Timur - Via Amiria; M. Cholid Mawardi; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The purpose of this study was to determine the effect of using regional financial accounting information systems and internal control systems on the quality of local government financial reports in a village, Tambak Gresik District, East Java. This research uses primary data in the form of questionnaire results. While the informants Head of the Financial Subdivision of the Regional Work Unit (SKPD), the Treasurer of each regional work unit (SKPD), the Accounting/Bookkeeping/Finance Staff of the Regional Work Unit (SKPD), and the Head of Administration/Work Unit Secretary Regional Devices (SKPD). This study used a non-probability sampling technique, namely purposive sampling with a total population of 52 respondents. The data analysis technique used in this research is multiple linear regression. The results of this study indicate that the utilization of regional financial accounting information systems and internal control systems has a partial effect on the quality of local government financial reports.Keywords: Utilization of regional financial accounting information systems, internal control systems, quality of local government financial reports